The Fluoroquinolone Finafloxacin Protects BALB/c Mice Against an Intranasal Infection With Francisella tularensis Strain SchuS4 - Barnes, Kay B.; Hamblin, Karleigh A.; Richards, Mark I.; Laws, Thomas R.; Vente, Andreas; Atkins, Helen S.; Harding, Sarah V. (Frontiers in Microbiology, 2019)
The efficacy of the novel fluoroquinolone finafloxacin was evaluated as a potential therapeutic in vitro and in vivo, following an intranasal infection of Francisella tularensis strain SchuS4 in BALB/c mice. We demonstrated that short treatment courses of finafloxacin provide high levels of protection, with a single dose resulting in a significant increase in time to death when compared to ciprofloxacin. In addition, following investigation into the window of opportunity for treatment, we have shown that finafloxacin can provide protection when administered up to 96 hours post-challenge. This is particularly encouraging since mice displayed severe signs of disease at this time point. In summary, finafloxacin may be a promising therapy for use in the event of exposure to F. tularensis, perhaps enabling the treatment regimen to be shortened or if therapy is delayed. The efficacy of finafloxacin against other biological threat agents also warrants investigation.